(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract examines the historical significance of the Mongol invasion and subsequent resistance against Mongol oppression across Eurasia during the 13th century. The Mongol Empire, under leaders like Genghis Khan, rapidly expanded through conquest, employing brutal tactics and subjugating vast territories. However, the narrative extends beyond conquest to highlight the diverse strategies of resistance adopted by local populations, ranging from guerrilla warfare to diplomatic alliances. The aftermath of Mongol rule saw the resurgence of independent states and cultural renaissance, reflecting the enduring human spirit in the face of adversity. This study underscores the complex interplay between conquest and cultural exchange, illustrating the profound impact of the Mongol era on shaping global history and interconnectedness. The lessons learned from this period resonate as timeless reminders of human resilience and the pursuit of freedom against overwhelming odds.